Analisis Kapasitas Fungsional Perawat Dan Bidan RSUD Kota Surakarta Dalam Pengembangan Program Hospital Preparedness For Emergency And Disaster - Akhmad Rifai; Addi Mardi Harnanto (Interest : Jurnal Ilmu Kesehatan, 2016)
Abstract: Functional Capacity Of Nurses And Midwives, Hospital Preparedness For Emergency And Disaster. Indonesia is a country that lies between two major continents and two great oceans. In addition, Indonesian territory lies on the line ring of fire that led to a natural phenomenon caused many disasters. Nurses and midwives are the functional elements which has a very big role in the hospital. There are some facilities that disaster preparedness is not owned by the hospital as well as the absence of a forum specifically set up and implement management Hospital For Emergency And Disaster Preparedness in an integrated manner. The purpose of this study was to determine the functional capacity of nurses and midwives Hospital of Surakarta in the development of hospital programs for emergency and disaster preparedness. This research is a descriptive study that seeks to explain the preparedness of nurses and midwives in implementing management Hospital For Emergency And Disaster Preparedness integrally artery mean pressure with a cross-sectional approach through research hypothesis testing. The population was nurses and midwives were 30 samples using descriptive statistical tests. Based on the results of research and discussion, we can conclude that from the results of a study of 30 respondents can be drawn the conclusion that the majority of nurses and midwives have good knowledge in emergency preparedness. Of the 14 components of the contribution of nurses and midwives obtained several components that felt still less that of the formation of clusters and disaster preparedness team Suggestion. put forward in this study is terhadap education and training of nurses and midwives to improve management capacity in disaster preparedness